THE EFFECT OF TOTAL INTERNATIONAL TOURISM EXPENDITURE AND TOTAL INVESTMENT IN THE TOURISM SECTOR ON GDP OF ASEAN COUNTRIES - Sony Pramaningtyas; Toto Gunarto; Arivina Ratih; I Wayan Suparta (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Tourism activities can contribute to regional revenues sourced from taxes, parking fees and tickets or can bring in foreign exchange from visiting foreign tourists. The existence of tourism will also grow economic businesses that interweave and support their activities so that they can increase people's income. This study will examine how the influence of foreign tourist spending and total investment in the tourism sector on GDP in 9 ASEAN countries. This study combines time series and cross section data, while the time series data used is data from 2014-2018 and the cross section covers 9 countries in ASEAN consisting of Indonesia, Malaysia, Singapore, Brunei Darussalam, Laos, Thailand, Philippines, Cambodia and Vietnam. The data in this study were obtained from the World Bank and the WTO. This research uses panel data regression analysis method. The results obtained in this study indicate that International Tourism Expenditure and Total Investment in Tourism Sector have a significant positive effect on GDP in 9 ASEAN countries.